Veloporphyrellus latisporus (Boletaceae), a new species from moist temperate forests of Pakistan. (1st October 2021) - Khan, Junaid; Ullah, Sadiq; Sher, Hassan; Fiaz, Muhammad; Khalid, Abdul Nasir
Abstract : Veloporphyrellus latisporus is proposed as a new species based on morphological characters and supporting molecular data from the ITS and LSU regions of the nuclear DNA. The new species is characterized by its red to reddish brown granulose pileus and comparatively broader basidiospores. A key to the species of Veloporphyrellus is provided. This is the first report of any Veloporphyrellus species from Pakistan.